Spatial and Temporal Variation of Rainfall in Ninava Governorate - Lamia M. F. Mustafa (College of Education for Pure Sciences, 2012)
Abstract Rainfall was studied in four locations in Ninava Governorate which are Mosul, Sinjar and Talafar and Rabea for the period (1974 - 2002). The Mean Monthly, Seasonally and Annual values of Rainfall, Standard Deviation, Coefficient of Variation and Time Series for rainfall was studied during there periods in all locations. Simple and Multiple correlations were found between mean monthly values of rainfall and other Metrological elements (Temperature, Relative humidity, Atmospheric pressure, Sunshine, Evaporation, Gloudness). Frequency distribution of rainfall data were also calculated. The results indicate a simple negative trends in the Time Series of the mean monthly values of rainfall in all locations, The maximum mean annual value of rainfall were found in sinjar location which reach (389) mm. The maximum frequency of rainfall in Oct., Nov., Apr., May were in the range of (0-30) mm in all stations while Dec., Jan., Feb., March show the maximum frequency in the range of (30-60) mm.